Etiology of bacterial soft rot of Orchids. - Abdullah, Hiryati; Kadzimin, Saleh (Universiti Putra Malaysia Press, 1993)
Symptoms of bacterial soft rot were observed on the Phalaenopsis sp. and Dendrobium sp. orchids. The disease caused death in many plants, especially those of the Phalaenopsis sp. at the seedling stage and ofyoung plants. Bacteria were consistently isolated on diseased plants. Tests proved the pathogenicity of the isolates on orchids. Steps were camed out to complete Koch's postulate. Based on the cultural, physiological and biochemical properties the pathogen was identified as Erwinia chrysanthemi Burk., McFadden and Dimock 1953.